Awareness exposure and technology adoption: the case of orange-fleshed sweetpotato in West Africa. - Adekambi, S.; Abidin, P.E.; Okello, J.J.; Carey, E.E. (2018)
Commonly used innovation adoption models indirectly assume homogenous information flow across farmers, which is often not the case. For new and or not well known technologies such as Orange-fleshed sweetpotato (OFSP) varieties, awareness exposure plays an important role in farmers’ decision to adopt. OFSP varieties have been shown to be highly effective means of combating it at the community level because of its high pro-vitamin A content and its cost effectiveness as compared with fortification and supplementation. Significant efforts, including the implementation of the Jumpstarting Orange-fleshed Sweetpotato project, have been deployed over the last decade in West Africa to promote the production and consumption of OFSP. Observations in the project countries indicating that the usage rate of OFSP among the beneficiaries was extremely high, suggesting a significant link between awareness activities and adoption behavior. Using the counterfactual outcome framework from the modern evaluation approach on 345 and 381 sweetpotato farmers from Ghana and Nigeria respectively, we found that the OFSP adoption rates could have been up to 61 percent in Ghana and 42 percent in Nigeria in 2016 instead of the observed sample adoption rate of 51 and 33 percent if the whole population was exposed to the OFSP varieties. This suggests that there is potential for increasing dissemination rate among population. Our study has showed that the OFSP adoption is influenced by a number of factors, which vary between the study countries. This implies that actions to increase the adoption rate shouldn’t be “one size fits all solution” approach.